Compósitos Portland-biopolímeros para cimentação de poços de petróleo - Bezerra, Ulisses Targino (2006)
The oil production in mature areas can be improved by advanced recovery techniques. In special, steam injection reduces the viscosity of heavy oils, thus improving its flow to surrounding wells. On the other hand, the usually high temperatures and pressures involved in the process may lead to cement cracking, negatively affecting both the mechanical stability and zonal isolation provided by the cement sheath of the well. The addition of plastic materials to the cement is an alternative to prevent this scenario. Composite slurries consisting of Portland cement and a natural biopolymer were studied. Samples containing different contents of biopolymer dispersed in a Portland cement matrix were prepared and evaluated by mechanical and rheological tests in order to assess their behavior according to API (American Petroleum Institute) guidelines. FEM was also applied to map the stress distribution encountered by the cement at bottom bole. The slurries were prepared according to a factorial experiment plan by varying three parameters, i.e., cement age, contents of biopolymer and water-to-cement ratio. The results revealed that the addition of the biopolymer reduced the volume of free water and the setting time of the slurry. In addition, tensile strength, compressive strength and toughness improved by 30% comparing hardened composites to plain Portland slurries. FEM results suggested that the stresses developed at bottomhole may be 10 to 100 times higher than the strength of the cement as evaluated in the lab by unconfined mechanical testing. An alternative approach is proposed to adapt the testing methodology used to evaluate the mechanical behavior of oilwell cement slurries by simulating the confined conditions encountered at bottornhole